Visualization of Seeking Identity on Transnational Children In “Be Prepared” Graphic Novel - Johanes Park (ULTIMART Jurnal Komunikasi Visual, 2023)
Be Prepared is a graphic novel about Vera, the daughter of immigrants from Russia. In her storyline, Vera faces many cultural challenges when dealing with American and other Russian immigrant children. Vera attempts to find identity amidst the differences between the original culture of Russia and the American culture as the country she lived in. The situation between 2 cultures is a challenge for transnational children. This study aims to analyze and see the meaning represented in the graphic novel, especially how transnational children obtain identity and adapt to their environment. The research method used in this research is semiotics and literature review. The semiotic method is used to see the relationship between signs to get the meaning. The semiotic theories used in this research are based on Roland Barthes’s theories. Another method is the literature review which is conducted by overviewing the signs through several published literature to expand the meanings. The base theory used in the literature review is a cultural study that consists of ideas about acculturation, immigration, and cross-cultural theories. From this research, it can be seen that in the comparison of situations of 2 birthday parties, there are expectations in acculturation. The worship scene in the Russian Orthodox church represents immigrant families' coping mechanism for acculturation stress. The signs seen in the graphic novel are also seen in the acculturation stage of Vera's character to gain identity, which can be divided into three stages, namely, the stage of seeking recognition, the stage of imitating, and the stage of integration. Keywords: transnationalism; immigrant; acculturation; graphic novel; sequential arts.